Revaccination in Pediatric Oncology Patients: One Center Experience - Yilmazbas, Pinar (Eurasian J Med, 2021)
OBJECTIVE: After chemotherapy, cancer survivors suffer from acquired immunological defects and become vulnerable to vaccine-preventable diseases. There are no universally approved revaccination guidelines for non-transplanted oncology patients. This study aimed to share our experience of revaccination in childhood cancer survivors to plan future vaccination schedules. MATERIALS AND METHODS: This retrospective study was conducted in a Pediatric Oncology Department of a university-affiliated hospital. Patients who were diagnosed with malignancy other than leukemia constituted the study population. Patients were directed for revaccination 6 months after the cessation of treatment. Revaccination was performed according to patients’ vaccination status before chemotherapy and seronegativity. RESULTS: Of the 64 patients in the study, 44 (68.75%) were boys. The mean age at the time of diagnosis and at start of vaccination was 8.8±5.3 years and 10.6±5.1 years, respectively. Hodgkin’s lymphoma was the most common diagnosis. The vaccination schedule of 7 patients was interrupted because of chemotherapy; after completing the missing vaccine doses, the serology of 2 patients was negative for at least 2 antigens. The vaccination schedule of 57 patients was completed before beginning chemotherapy and 52 of them were seronegative for at least 1 antigen. No adverse reactions or life-threatening infections were observed because of vaccinations. CONCLUSION: There are different approaches when vaccinating the oncology patients after chemotherapy. Watching out for the four touchstones mentioned in our study will protect the patient and do no harm. More studies are needed to constitute universal and standardized revaccination guidelines for these patients.